Deconfining transition in Full QCD - Biagio Lucini (Nuclear Physics B - Proceedings Supplements, 2002)
We present evidence that in full QCD with two dynamical quarks confinement is produced by dual superconductivity of the vacuum as in the quenched theory. Preliminary information is obtained on the nature of the deconfining transition.